ANALISIS PRESEPSI MASYARAKAT : APLIKASI KONSEP BALANCE SCORECARD DI KANTOR BERSAMA SAMSAT WILAYAH PROVINSI MALUKU UTARA - Fazry Sidiq (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
This research discuses about performance measurement of organization by using Balanced Scorecard as a method that can be applied in a public sectororganization. Nowadays, performance measurement in public sector is still morefocused on internal business and short term goals (financial). Therefore,measurement of performance using the Balanced Scorecard (financialperspective, customer perspective, internal business perspective and learning and growth perspective) offers a solution for more comprehensive performancemeasurement and comprehensive in an organization. The object of this research is Samsat Office North Maluku. The research at samsat office conducted by comparing between internal samsat performance and Balanced Scorecard performance of the years 2009-2011.From the results of research using the Balanced Scorecard, the average value for each perspectives of financial, customer, internal business and learning andgrowth is good enough. So it can be concluded that the performance of the Samsat office North Maluku included in the criteria sufficiently, with some suggestions and improvements that need to be done.